Implementation of the Lean Manufacturing Concept to Reduce Waste in Spare Part Repair Activities at PT. X - Subandi; Danang Darunanto; Sumirahwati; Rr. Endang Wahyuni; Deslida Saidah; Irma Binarti (International Journal of Science and Society, 2023)
The competition in the manufacturing industry is currently moving very fast. Competitive advantage, increased production effectiveness in operational activities, continuous performance improvement and business strategy Good quality is something that manufacturing companies must pay attention to to be able to compete globally. PT.X is a manufacturing company that specializes in repairing Automated Teller Machine (ATM) machine spare parts. In the process of repairing this spare part, there are problems with the use of the application system, the number of parts that cannot be repaired as before and the performance of employees is lacking, causing waste. This waste has an impact on performance and operational activities being not optimal and hampering the process of repairing spare parts. The lean manufacturing approach aims to identify and eliminate waste that occurs during operational activities in order to be more efficient and effective with the method Value Stream Mapping (VSM) for mapping the flow of spare part repairs and information flow, identifying waste which is divided into 7 categories and conducting analysis. The root cause of waste with fishbone diagrams, the result of which is the cause of waste by humans, is the lack of insight or knowledge of employees, machines that are damaged due to continuous use and the methods used by the company are not appropriate. The results of the identification of waste are waste waiting, transportation, processing, inventory and defective products. Keywords: Lean Manufacturing, Waste, Value Stream Mapping, Fishbone Diagram.